1981
DOI: 10.1111/j.1476-5381.1981.tb09102.x
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Polymyxin B at the Frog Neuromuscular Junction

Abstract: I The effects of polymyxin B at the neuromuscular junction of the frog were studied by conventional electrophysiological and voltage clamp techniques.2 At a concentration of 2.5 jig/ml polymyxin B produced neuromuscular blockade in 10 to 15 min and endplate potentials (e.p.ps) could be recorded. Resting membrane potential was unaffected. The neuromuscular block was characterized by a depressed e.p.p. quantal content (28 ± 7), which was similar to that determined from endplates exposed to 13 mm magnesium (23 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
1

Year Published

1983
1983
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
2
6
1
Order By: Relevance
“…The concentration-dependent decrease in amplitude of MEPPs in TIMG endplates by the PKC inhibitor PMB confirmed the results of another study that reported a postsynaptic effect of PMB (Durant & Lambert, 1981). PMB also exerted a presynaptic effect, namely an increase of the MEPP frequency.…”
Section: Inhibition Of Pkcsupporting
confidence: 88%
“…The concentration-dependent decrease in amplitude of MEPPs in TIMG endplates by the PKC inhibitor PMB confirmed the results of another study that reported a postsynaptic effect of PMB (Durant & Lambert, 1981). PMB also exerted a presynaptic effect, namely an increase of the MEPP frequency.…”
Section: Inhibition Of Pkcsupporting
confidence: 88%
“…The effects of PXB at the frog neuromuscular junction have also been studied. PXB is a very potent neuromuscular block whose effects can be partially reversed by addition of calcium (Durant and Lambert, 1981). These studies indicate that PXB influences both structural and physiological properties of the intact cell.…”
mentioning
confidence: 83%
“…myasthenia gravis, tubocurarine paralysis). Certainly, 4-aminopyridine seems to be a better antagonist of antibiotics that block transmission predominantly by a prejunctional mechanism (aminoglycosides, polymyxins) than of those that act by a post junctional mechanism (tetracyclines, certain lincosamides) (SOBEK et al 1968;SINGH et al 1978 a, b;LEE et al 1978;MAENO and ENOMOTO 1980;ENOMOTO and MAENO 1981;UCHIYAMA et al 1981;DURANT and LAMBERT 1981). Aminopyridines are also very effective against the depression of transmitter release in experimental botulism LUNDH 1978b;TAZIEFF-DEPIERRE et al 1978;SIMPSON 1978;MOLGO et al 1980), or that produced by crotoxin (VITAL-BRAZIL et al 1979).…”
Section: Repetitive Nerve Stimulationmentioning
confidence: 97%